2007
DOI: 10.1088/0022-3727/40/15/019
|View full text |Cite
|
Sign up to set email alerts
|

Plasma decay in N2, CO2and H2O excited by high-voltage nanosecond discharge

Abstract: Plasma decay after a high-voltage nanosecond discharge was studied experimentally and numerically in room temperature N2, CO2 and H2O for pressures between 1 and 10 Torr. The time-resolved electron density was measured by a microwave interferometer for initial electron densities in the range 8 × 1011–3 × 1012 cm−3 and the effective electron–ion recombination coefficient was determined. It was shown that this coefficient varies in time and depends on pressure. A numerical simulation was carried out to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 37 publications
2
34
0
1
Order By: Relevance
“…Therefore, the lifetime of the plasma was overestimated in [Schneider et al, 2004] approximately by an order of magnitude. This follows also from direct measurements of the effective recombination rates in room temperature N 2 , CO 2 and H 2 O under conditions close to those for MHD-controlled inlets were performed in papers ( [Zhukov et al, 2006;Aleksandrov et al, 2007aAleksandrov et al, ,2007bAleksandrov et al, ,2008Aleksandrov et al, ,2009), and in air in paper [Aleksandrov et al, 2011]. Discharge was initiated in a quartz tube of inner diameter 47 mm and outer diameter 50 mm, the metallic electrodes being at the ends of the tube.…”
Section: Mhd Flow Controlmentioning
confidence: 76%
See 4 more Smart Citations
“…Therefore, the lifetime of the plasma was overestimated in [Schneider et al, 2004] approximately by an order of magnitude. This follows also from direct measurements of the effective recombination rates in room temperature N 2 , CO 2 and H 2 O under conditions close to those for MHD-controlled inlets were performed in papers ( [Zhukov et al, 2006;Aleksandrov et al, 2007aAleksandrov et al, ,2007bAleksandrov et al, ,2008Aleksandrov et al, ,2009), and in air in paper [Aleksandrov et al, 2011]. Discharge was initiated in a quartz tube of inner diameter 47 mm and outer diameter 50 mm, the metallic electrodes being at the ends of the tube.…”
Section: Mhd Flow Controlmentioning
confidence: 76%
“…In this case, O 4 + ions have no time to form from O 2 + ions in the discharge phase and in the discharge afterglow. However, measurements [Aleksandrov et al, 2011] showed that in this case the predominance of O 2 + ions does not necessarily lead to increasing the lifetime of the air plasma. Let us consider this point in more detail.…”
Section: Mhd Flow Controlmentioning
confidence: 88%
See 3 more Smart Citations